2013
DOI: 10.1161/hypertensionaha.112.201434
|View full text |Cite
|
Sign up to set email alerts
|

A Role for TRPV1 in Influencing the Onset of Cardiovascular Disease in Obesity

Abstract: Obesity induced by Western diets is associated with type 2 diabetes mellitus and cardiovascular diseases, although underlying mechanisms are unclear. We investigated a murine model of diet-induced obesity to determine the effect of transient potential receptor vanilloid 1 (TRPV1) deletion on hypertension and metabolic syndrome. Wild-type and TRPV1 knockout mice were fed normal or high-fat diet from 3 to 15 weeks. High-fat diet-fed mice from both genotypes became obese, with similar increases in body and adipos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
77
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(84 citation statements)
references
References 34 publications
7
77
0
Order By: Relevance
“…The catheter was secured using surgical braided silk (5.0, waxed sutures, Pearsalls Ltd, UK) and the transmitter was placed subcutaneously in the right flank. The abdominal wall and the skin incision were sutured separately using absorbable sutures (Vicryl 5.0; Ethicon, Johnson & Johnson) 29. For measurement of temperature, the transmitter (TA10TA‐F10; DSI) was inserted.…”
Section: Methodsmentioning
confidence: 99%
“…The catheter was secured using surgical braided silk (5.0, waxed sutures, Pearsalls Ltd, UK) and the transmitter was placed subcutaneously in the right flank. The abdominal wall and the skin incision were sutured separately using absorbable sutures (Vicryl 5.0; Ethicon, Johnson & Johnson) 29. For measurement of temperature, the transmitter (TA10TA‐F10; DSI) was inserted.…”
Section: Methodsmentioning
confidence: 99%
“…Male Sprague Dawley rats (150 -250 g; Charles River) were used. Brains were removed under deep isoflurane anesthesia (5%), and hindbrain slices were prepared as described previously (Doyle and Andresen, 2001). Briefly, a wedge of ventral brainstem was removed to tilt the hindbrain so that horizontal slices (250 m) contained the ST in the same plane as cell bodies in the caudal NTS (VT-1000S vibrating microtome from Leica; and sapphire blade from Delaware Diamond Knives).…”
Section: Methodsmentioning
confidence: 99%
“…The latency was measured from the stimulus shock to the onset of the first EPSC evoked in each burst, and the jitter was then calculated as SD of the latency and averaged across Ն30 ST shocks. These low-jitter (Ͻ200 s), consistent-waveform EPSCs were selected for study as a monosynaptic unitary ST afferent input (Doyle and Andresen, 2001;Bailey et al, 2006a). Capsaicin (CAP; 100 nM) tests were conducted at the end of each experiment to verify vanilloidsensitive (TRPV1 ϩ ) or vanilloid-insensitive (TRPV1 Ϫ ) afferents (Doyle and Andresen, 2001;Bailey et al, 2006a;.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study found no difference in weight gain between TRPV1 knockout and wild-type mice kept on a high-fat diet (Marshall et al, 2013). These seemingly contradictory findings may be reconciled by a recent study in which the phenotype of TRPV1 knockout mouse was 1) dependent on the age of the animals and 2) was also heavily influenced by environmental variables (diet, room temperature, etc) that can impact thermoregulation (Wanner et al, 2011).…”
Section: E Transient Receptor Potential Channels In Obesity and Metamentioning
confidence: 98%